Geothermal energy recovery from abandoned petroleum wells: A review of the challenges and opportunities; Sustainable Energy Technologies and Assessments; Vol. 68 - Davoodi Sh. Shadfar; Al-Shargabi M. A. T. S. Mokhammed Abdulsalam Takha Sallam; Wood D. A. David; Slivkin S. S. Stanislav Sergeevich; Shishaev G. Yu. Gleb Yurievich; Rukavishnikov V. S. Valery Sergeevich (2024, 2024)
Title screen